Adhesive composition for surface protection and surface protective film
The pressure-sensitive adhesive composition, featuring a specific copolymer and oligomer blend, addresses the issue of zipping during peeling of surface protection films for electronic devices by balancing heat resistance and retention, ensuring effective surface protection.
Patent Information
- Application Number
- JP2023149956
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-28
AI Technical Summary
Existing surface protection films for electronic devices face issues with zipping during peeling, especially after heat treatment, due to high peeling forces, which can damage the product and reduce quality.
A pressure-sensitive adhesive composition comprising a copolymer of alkyl (meth)acrylate, a (meth)acrylic polymer with a specific glass transition temperature range, and a nitrogen atom-containing monomer, along with a (meth)acrylic oligomer, which balances heat resistance and retention while suppressing zipping during peeling.
The adhesive composition achieves an excellent balance of heat resistance and retention, effectively suppresses zipping during peeling even after heat treatment, and minimizes surface contamination of the adherend.
Smart Images

Figure 2025042811000001 
Figure 2025042811000002 
Figure 2025042811000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a pressure-sensitive adhesive composition for protecting a surface and a surface protective film. [Background technology]
[0002] 2. Description of the Related Art In the manufacturing process of electronic devices, surface protective films are used to prevent the occurrence of defective products and deterioration of product quality due to surface dirt, damage, and the like.
[0003] The unnecessary surface protection film is peeled off, but at this time, if the peeling speed is fast, zipping may occur. If zipping occurs, the product may be damaged, leading to a deterioration in quality. In particular, when a heat treatment process at high temperatures is included as part of the manufacturing process, the heat treatment process increases the peeling force of the surface protection film, making zipping more likely to occur during peeling. In addition, an increase in peeling force also leads to a deterioration in workability in peeling.
[0004] Patent Document 1 describes a pressure-sensitive adhesive using two types of (meth)acrylic polymers with different substituents, which exhibits excellent adhesion to plastics. However, it requires an extremely large peeling force when peeled at high speed, and is prone to zipping, making it unsuitable for use as a surface protection film for electronic devices.
[0005] Furthermore, Patent Document 2 describes an adhesive in which a small amount of a plasticizer such as polyester is added to an acrylic adhesive. However, even with an adhesive of this composition, the peel force during high speed peeling is still large, and the holding power is insufficient, which can result in problems such as lifting and peeling. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 10-310754 [Patent Document 2] JP 2000-328016 A Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a pressure-sensitive adhesive composition for protecting surfaces which has an excellent balance of adhesive properties such as heat resistance and holding power, is capable of suppressing zipping during peeling even when heat treatment is applied, and is unlikely to contaminate the surface of an adherend. [Means for solving the problem]
[0008] As a result of intensive research aimed at solving the above problems, the present inventors have found that the above problems can be solved by the following embodiments, and have completed the present invention.
[0009] [1] A pressure-sensitive adhesive composition for protecting a surface, comprising: a (meth)acrylic polymer (A) which is a copolymer of a monomer mixture (a) containing 5% by mass or more and less than 20% by mass of an alkyl (meth)acrylate having 1 to 3 carbon atoms in the ester side chain, the (meth)acrylic polymer (A) having a glass transition temperature (Tg) of -70°C or more and -25°C or less; and a monomer mixture (b) which contains a nitrogen atom-containing monomer, and a (meth)acrylic oligomer (B) which has a glass transition temperature (Tg) of more than -25°C or less and 200°C or less, the (meth)acrylic oligomer (B) being contained in an amount of more than 0 part by mass and not more than 40 parts by mass per 100 parts by mass of the (meth)acrylic polymer (A). [2] The pressure-sensitive adhesive composition for protecting a surface according to item [1], wherein the monomer mixture (a) further contains an alkyl(meth)acrylate having 6 to 22 carbon atoms in the ester side chain in a range of 50% by mass or more and less than 94% by mass, and a carboxy group-containing monomer in a range of more than 1% by mass and 10% by mass or less (wherein the entire monomer mixture (a) is taken as 100% by mass). [3] The pressure-sensitive adhesive composition for protecting a surface according to item [1] or [2], wherein the monomer mixture (b) contains the nitrogen atom-containing monomer in an amount of more than 0 mass% and not more than 10 mass% (where the total of the monomer mixture (b) is taken as 100 mass%). [4] A pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition for protecting a surface according to any one of items [1] to [3], which has a biomass ratio of 10% or more. [5] A surface protection film having a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition for protecting a surface according to any one of items [1] to [3]. [6] The surface protection film according to item [5], in which the amount of displacement after one hour of a holding strength test in accordance with JIS Z 0237:2009, with an application area of 20 mm x 20 mm, a test temperature of 80°C, and a load of 1 kg, is 1.5 mm or less. Effect of the Invention
[0010] According to the present invention, it is possible to provide a pressure-sensitive adhesive composition for protecting surfaces which has an excellent balance of adhesive properties such as heat resistance and holding power, is capable of suppressing zipping during peeling even when heat treatment is applied, and is unlikely to contaminate the surface of the adherend. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below. In the present invention, "(meth)acrylic" is used to collectively refer to acrylic and methacrylic. That is, "(meth)acrylic acid alkyl ester" is used to collectively refer to acrylic acid alkyl ester and methacrylic acid alkyl ester. Also, "(meth)acrylate" is used to collectively refer to acrylate and methacrylate. Also, in the present invention, A to B representing a numerical range means A or more and B or less, unless otherwise specified.
[0012] <<Adhesive composition for surface protection>> The pressure-sensitive adhesive composition for protecting a surface according to the present invention (hereinafter also referred to as "the composition") is a copolymer of a monomer mixture (a) containing 5% by mass or more and less than 20% by mass of an alkyl (meth)acrylate (hereinafter also referred to as "monomer (a1)") having 1 to 3 carbon atoms in the ester side chain, and is a copolymer of a (meth)acrylic polymer (A) having a glass transition temperature (Tg) of -70°C or more and -25°C or less, and a monomer mixture (b) containing a nitrogen atom-containing monomer, and contains a (meth)acrylic oligomer (B) having a glass transition temperature (Tg) of more than -25°C or less and 200°C or less, and the (meth)acrylic oligomer (B) is contained in an amount of more than 0 part by mass and not more than 40 parts by mass per 100 parts by mass of the (meth)acrylic polymer (A). A surface protection film having an adhesive layer formed from the surface protection adhesive composition of the present invention is preferred because it has an excellent balance of heat resistance, holding power, etc., can suppress zipping during peeling even when heat treatment is applied, and is less likely to contaminate the surface of the substrate.
[0013] <(Meth)acrylic polymer (A)> The (meth)acrylic polymer (A) is a copolymer of a monomer mixture (a) containing 5% by mass or more and less than 20% by mass of the monomer (a1), and has a glass transition temperature (Tg) of -70°C or more and -25°C or less. The (meth)acrylic polymer (A) used in the present composition may be one type or two or more types.
[0014] The Tg of the polymer (A) is usually from -70°C to -25°C, preferably from -67°C to -30°C, and more preferably from -63°C to -35°C. When the Tg of the polymer (A) is within the above range, a surface protection film having an appropriate peel strength can be easily obtained, which is preferable. The method for measuring Tg in this specification is as described in the Examples section below.
[0015] The weight average molecular weight (Mw) of the polymer (A) measured by gel permeation chromatography (GPC) is not particularly limited, but is preferably from 200,000 to 2,000,000, more preferably from 300,000 to 1,600,000, and particularly preferably from 400,000 to 1,200,000. When the Mw of the polymer (A) is within the above range, the adhesive layer formed from the adhesive composition has excellent durability and a suitable cohesive force, and the adhesive composition has a good viscosity and good coatability. The method for measuring the Mw of the polymer in this specification is as described in the Examples section below.
[0016] The monomer (a1) is not particularly limited as long as it can change the Tg of the polymer (A) to -70°C or more and -25°C or less. Preferred are methyl (meth)acrylate, ethyl (meth)acrylate, and propyl (meth)acrylate, and more preferably methyl (meth)acrylate.
[0017] The monomer mixture (a) contains the monomer (a1) in an amount of usually 5% by mass or more and less than 20% by mass, preferably 6% by mass or more and 15% by mass or less, and more preferably 7% by mass or more and 12% by mass or less, where the total amount of the monomer mixture (a) is taken as 100% by mass. When the content of the monomer (a1) is within the above range, an excessive increase in high-speed peel strength after heat treatment is suppressed, and zipping is less likely to occur, which is preferable.
[0018] The monomer mixture (a) may further contain an alkyl(meth)acrylate having an ester side chain with 6 to 22 carbon atoms (hereinafter, also referred to as "monomer (a2)"). The monomer (a2) is not particularly limited as long as it can set the Tg of the polymer (A) to -70°C or more and -25°C or less. Preferred are hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate, and behenyl (meth)acrylate, more preferred are octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate, and behenyl (meth)acrylate, and even more preferred are octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, and stearyl (meth)acrylate. In particular, from the viewpoint of reducing the environmental load, it is preferable to include a structural unit derived from biomass, for example, octyl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate, etc., which are produced using raw materials derived from biomass. These can be obtained, for example, by reacting (meth)acrylic acid with an alcohol derived from biomass. The biomass degree of an alkyl (meth)acrylate containing a structural unit derived from biomass is calculated by the ratio of the structural unit derived from biomass to the alkyl (meth)acrylate containing a structural unit derived from biomass, calculated by weight ratio. The alkyl group may be a linear alkyl group or a branched alkyl group. The monomer (a2) may be used alone or in combination of two or more kinds.
[0019] The monomer mixture (a) contains the monomer (a2) in an amount of usually 50% by mass or more and less than 94% by mass, preferably 55% by mass or more and 92% by mass or less, and more preferably 60% by mass or more and 90% by mass or less, where the total amount of the monomer mixture (a) is taken as 100% by mass. When the content of the monomer (a2) is within the above range, an excessive increase in high-speed peel strength after heat treatment is suppressed, and excellent heat resistance is achieved, which is more preferable.
[0020] The monomer mixture (a) may further contain a carboxyl group-containing monomer (hereinafter, also referred to as "monomer (a3)"). The monomer (a3) is not particularly limited as long as it can set the Tg of the polymer (A) to -70°C or more and -25°C or less, but is preferably (meth)acrylic acid. The monomer (a3) may be used alone or in combination of two or more.
[0021] The monomer mixture (a) contains the monomer (a3) in an amount generally greater than 0 mass% and less than 10 mass%, preferably greater than 1 mass% and less than 9 mass%, more preferably greater than 1 mass% and less than 8 mass%, where the total of the monomer mixture (a) is taken as 100 mass%. When the monomer (a3) is within the above range, a cohesive force is generated in the pressure-sensitive adhesive layer due to interaction with the oligomer (B) described later, which is preferable because it provides excellent holding power and reduces contamination of the adherend surface even after heat treatment.
[0022] The monomer mixture (a) may further contain a monomer (hereinafter also referred to as "monomer (a4)") other than the monomers (a1), (a2) and (a3).
[0023] The monomer (a4) is not particularly limited as long as it can change the Tg of the polymer (A) to -70°C or more and -25°C or less. Examples of the monomer (a4) include alkyl (meth)acrylates having 4 to 5 carbon atoms in the ester side chain, such as butyl (meth)acrylate and pentyl (meth)acrylate: 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, 4-ethoxybutyl (meth)acrylate, and the like. Alkoxyalkyl (meth)acrylates such as acrylate: 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate and other hydroxyl group-containing (meth)acrylates: cyclohexyl (meth)acrylate, isobornyl (meth)acrylate and other cyclic alkyl group-containing (meth)acrylates: benzyl (meth)acrylate, phenyl (meth)acrylate, phenoxy Aromatic ring-containing (meth)acrylates such as diethyl (meth)acrylate: Amino group-containing monomers such as N,N-dimethylaminoethyl (meth)acrylate and N,N-diethylaminoethyl (meth)acrylate: Amino group-containing monomers such as (meth)acrylamide, N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-propyl (meth)acrylamide, N-hexyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide and N,N-diethyl (meth)acrylamide: N-vinylpyrrolidone, N Nitrogen-based heterocycle-containing monomers such as vinyl caprolactam and (meth)acryloylmorpholine; vinyl esters such as vinyl acetate and vinyl propionate; olefins such as ethylene, propylene and isobutylene; halogenated olefins such as vinyl chloride and vinylidene chloride; styrene-based monomers such as styrene and α-methylstyrene; diene-based monomers such as butadiene, isoprene and chloroprene; nitrile-based monomers such as (meth)acrylonitrile; and macromonomers having a number average molecular weight (Mn) of 500 to 100,000 and having a polymerizable unsaturated group. The monomer (a4) may be used alone or in combination of two or more kinds.
[0024] The monomer mixture (a) contains the monomer (a4) in an amount of preferably 40% by mass or less, more preferably 30% by mass or less, and further preferably 20% by mass or less, where the total amount of the monomer mixture (a) is taken as 100% by mass.
[0025] <Method for producing (meth)acrylic polymer (A)> The (meth)acrylic polymer (A) according to the present invention is obtained by copolymerizing the monomer mixture (a). The production method is not particularly limited, and any known method can be used, for example, solution polymerization, bulk polymerization, emulsion polymerization, suspension polymerization, etc., and is preferably the solution polymerization method because it is easy to adjust the molecular weight and produces fewer impurities during production.
[0026] Specifically, a polymerization solvent and a monomer mixture (a) are charged into a reaction vessel, a polymerization initiator is added under an atmosphere of an inert gas such as nitrogen gas, the reaction initiation temperature is set to usually 40 to 100°C, preferably 50 to 90°C, and the reaction system is maintained at a temperature of usually 50 to 90°C, preferably 60 to 90°C, and the reaction is allowed to proceed for 3 to 20 hours to obtain a (meth)acrylic polymer (A).
[0027] Examples of the polymerization initiator include an azo-based initiator and a peroxide-based polymerization initiator. Examples of the azo initiator include 2,2'-azobisisobutyronitrile, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2-cyclopropylpropionitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2-(carbamoylazo)isobutyronitrile, 2-phenylazo-4-methoxy-2,4-dimethylvaleronitrile, 2,2'-azobis(2 -Amidinopropane) dihydrochloride, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)-propionamide], 2,2'-azobis(isobutylamide) dihydrate, 4,4'-azobis(4-cyanopentanoic acid), 2,2'-azobis(2-cyanopropanol), dimethyl-2,2'-azobis(2-methylpropionate), and 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)propionamide).
[0028] Examples of peroxide-based polymerization initiators include t-butyl hydroperoxide, cumene hydroperoxide, dicumyl peroxide, benzoyl peroxide, lauroyl peroxide, caproyl peroxide, di-i-propyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, t-butyl peroxypivalate, and 2,2-bis(4,4-di-t-butylperoxycyclohexyl). Examples of the alkylperoxycyclohexyl include propane, 2,2-bis(4,4-di-t-amylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-octylperoxycyclohexyl)propane, 2,2-bis(4,4-di-α-cumylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)butane, and 2,2-bis(4,4-di-t-octylperoxycyclohexyl)butane.
[0029] The polymerization initiator may be used alone or in combination of two or more kinds. In addition, there is no restriction on adding the polymerization initiator multiple times during the polymerization. The polymerization initiator is used in an amount of usually 0.001 to 5 parts by mass, preferably 0.005 to 3 parts by mass, based on 100 parts by mass of the monomer components forming the (meth)acrylic copolymer (A). In addition, during the polymerization reaction, the polymerization initiator, the chain transfer agent, the polymerizable monomer, and the polymerization solvent may be appropriately added.
[0030] Examples of the polymerization solvent used in the solution polymerization include aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as n-pentane, n-hexane, n-heptane, and n-octane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, cycloheptane, and cyclooctane; ethers such as diethyl ether, diisopropyl ether, 1,2-dimethoxyethane, dibutyl ether, tetrahydrofuran, dioxane, anisole, phenylethyl ether, and diphenyl ether; halogenated hydrocarbons such as chloroform, carbon tetrachloride, 1,2-dichloroethane, and chlorobenzene; esters such as ethyl acetate, propyl acetate, butyl acetate, and methyl propionate; ketones such as acetone, methyl ethyl ketone, diethyl ketone, methyl isobutyl ketone, and cyclohexanone; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; nitriles such as acetonitrile and benzonitrile; and sulfoxides such as dimethyl sulfoxide and sulfolane. The polymerization solvent may be used alone or in combination of two or more.
[0031] <(Meth)acrylic oligomer (B)> The (meth)acrylic oligomer (B) is a copolymer of a monomer mixture (b) containing a nitrogen atom-containing monomer (hereinafter also referred to as "monomer (b1)"), and has a Tg of more than -25°C and 200°C or less. The (meth)acrylic oligomer (B) used in the present composition may be one type or two or more types.
[0032] The Tg of the oligomer (B) is usually higher than -25°C and not higher than 200°C, preferably 0°C or higher and 180°C or lower, and more preferably 50°C or higher and 150°C or lower. When the Tg of the oligomer (B) is within the above range, the peel force during high speed peeling can be easily adjusted to an appropriate range, and lifting and peeling can be prevented, which is preferable.
[0033] The Mw of the oligomer (B) is usually from 1,000 to 50,000, and preferably from 3,000 to 30,000. It is preferable that the Mw of the oligomer (B) is within the above range, since the compatibility with the polymer (A) is excellent.
[0034] The content of the oligomer (B) is usually more than 0 parts by mass and not more than 40 parts by mass, preferably 1 part by mass or more and not more than 35 parts by mass, more preferably 2 parts by mass or more and not more than 30 parts by mass, relative to 100 parts by mass of the polymer (A). When the content of the oligomer (B) is within the above range, peel speed dependency (change in peel force depending on peel speed) is suppressed, which is preferable. This is thought to be because the distribution of the oligomer (B) is moderately biased toward the adherend side of the pressure-sensitive adhesive layer.
[0035] As the monomer (b1), any monomer containing nitrogen and a polymerizable double bond can be used without any particular limitation, and examples thereof include amino group-containing monomers, amide group-containing monomers, and nitrogen-based heterocycle-containing monomers. Among them, amino group-containing monomers are preferred, and amino group-containing monomers containing tertiary amines such as N,N-dimethylaminoethyl (meth)acrylate and N,N-diethylaminoethyl (meth)acrylate are more preferred. The monomer (b1) may be used alone or in combination of two or more. The amino group-containing monomer may be a monomer having one amino group or two or more amino groups in one molecule.
[0036] The monomer mixture (b) contains the monomer (b1) in an amount generally greater than 0 mass % and not greater than 10 mass %, preferably from 1 mass % to 9 mass %, more preferably from 2 mass % to 8 mass %, where the total of the monomer mixture (b) is taken as 100 mass %. When the monomer mixture (b) is within the above range, a cohesive force is generated in the pressure-sensitive adhesive layer due to interaction with the polymer (A), resulting in excellent holding power and reduced contamination of the adherend surface even after heat treatment, which is preferable.
[0037] The monomer mixture (b) may contain a (meth)acrylic acid alkyl ester (hereinafter also referred to as "monomer (b2)"). The monomer (b2) is not particularly limited as long as it can set the Tg of the oligomer (B) to more than -25°C and not more than 200°C, and examples of the monomer (b2) include the monomers described as the (meth)acrylic acid alkyl ester used in the polymer (A). The monomer (b2) may be used alone or in combination of two or more kinds.
[0038] The monomer mixture (b) may contain the monomer (b2) in an amount of usually 10% by mass or more and 99% by mass or less, preferably 20% by mass or more and 98% by mass or less, more preferably 30% by mass or more and 97% by mass or less, where the total amount of the monomer mixture (b) is taken as 100% by mass.
[0039] The monomer mixture (b) is not particularly limited as long as it can set the Tg to more than -25°C and not more than 200°C, and may contain a monomer (b1) and / or a monomer other than the monomer (b1) and the monomer (b2) (hereinafter also referred to as "monomer (b3)"). Examples of the monomer (b3) include alkoxyalkyl (meth)acrylates, hydroxyl group-containing (meth)acrylates, cyclic alkyl group-containing (meth)acrylates, aromatic ring-containing (meth)acrylates, vinyl esters, olefins, halogenated olefins, styrene-based monomers, diene-based monomers, nitrile-based monomers, and macromonomers, which are exemplified as the monomer (a4). The monomer (b3) may be used alone or in combination of two or more kinds.
[0040] The monomer mixture (b) may contain the monomer (b3) in an amount of usually less than 90 mass%, preferably 70 mass% or less, more preferably 50 mass% or less, where the total amount of the monomer mixture (b) is taken as 100 mass%.
[0041] <Method for producing (meth)acrylic oligomer (B)> The (meth)acrylic oligomer (B) according to the present invention is obtained by copolymerizing the monomer mixture (b). The production method is not particularly limited, and any known method can be used, for example, solution polymerization, bulk polymerization, emulsion polymerization, suspension polymerization, etc., and is preferably the solution polymerization method because it is easy to adjust the molecular weight and produces fewer impurities during production.
[0042] Specifically, a polymerization solvent and monomer components are charged into a reaction vessel, a polymerization initiator is added under an inert gas atmosphere such as nitrogen gas, the reaction initiation temperature is set to usually 40 to 100°C, preferably 50 to 90°C, and the reaction system is maintained at a temperature of usually 50 to 90°C, preferably 60 to 90°C, and the reaction is carried out for 4 to 20 hours to obtain a (meth)acrylic oligomer (B).
[0043] As the polymerization initiator, those described in the section on the production method of the (meth)acrylic polymer (A) can be appropriately used. The polymerization initiator used in producing the (meth)acrylic polymer (A) and the polymerization initiator used in producing the (meth)acrylic oligomer (B) may be the same or different.
[0044] The polymerization initiator is used in an amount of usually 0.001 to 5 parts by mass, preferably 0.005 to 3 parts by mass, based on 100 parts by mass of the monomer components forming the (meth)acrylic oligomer (B). In addition, during the polymerization reaction, the polymerization initiator, the chain transfer agent, the polymerizable monomer, and the polymerization solvent may be appropriately added.
[0045] As the polymerization solvent used in the solution polymerization, those described in the section on the method for producing the (meth)acrylic polymer (A) can be appropriately used. The polymerization solvent used in producing the (meth)acrylic polymer (A) and the polymerization solvent used in producing the (meth)acrylic oligomer (B) may be the same or different.
[0046] <Crosslinking agent (C)> The pressure-sensitive adhesive composition of the present invention may contain a crosslinking agent (C). The crosslinking agent (C) is not particularly limited, but may be an epoxy-based crosslinking agent, an isocyanate-based crosslinking agent, a metal chelate compound, or the like, and among these, an epoxy-based crosslinking agent is preferred. The crosslinking agent (C) used in the present composition may be one type alone, or two or more types may be used.
[0047] Examples of epoxy crosslinking agents include 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, N,N,N',N'-tetraglycyl-m-xylylenediamine, N,N,N',N'-tetraglycylaminophenylmethane, triglycidyl isocyanate, mN,N-diglycidylaminophenyl glycidyl ether, N,N-diglycidyl toluidine, N,N-diglycidyl aniline, pentaerythritol polyglycidyl ether, and 1,6-hexanediol diglycidyl ether.
[0048] Examples of the isocyanate crosslinking agent include isocyanate monomers such as tolylene diisocyanate, chlorophenylene diisocyanate, hexamethylene diisocyanate, tetramethylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, and hydrogenated diphenylmethane diisocyanate; isocyanate compounds obtained by addition reaction of these isocyanate monomers with trimethylolpropane or the like; biuret type isocyanate compounds; and urethane prepolymer type isocyanates obtained by addition reaction of isocyanate monomers with polyether polyol, polyester polyol, acrylic polyol, polybutadiene polyol, polyisoprene polyol, or the like.
[0049] Metal chelate compounds include compounds in which polyvalent metals such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, and zirconium are coordinated with alkoxides, acetylacetone, ethyl acetoacetate, etc. Specific examples include aluminum isopropylate, aluminum secondary butylate, aluminum ethyl acetoacetate diisopropylate, aluminum trisethyl acetoacetate, and aluminum trisacetylacetonate.
[0050] As the crosslinking agent, an epoxy-based crosslinking agent is preferred from the viewpoint of excellent heat resistance. The pressure-sensitive adhesive composition of the present invention is capable of forming a three-dimensional crosslinked structure by reaction of the crosslinking agent, and is capable of exhibiting an appropriate cohesive strength.
[0051] The content of the crosslinking agent (C) is preferably in the range of 0.01 parts by mass or more and 8 parts by mass or less, more preferably 0.01 parts by mass or more and 5 parts by mass or less, based on 100 parts by mass of the polymer (A). If the content of the crosslinking agent (C) is within the above range, it is preferable since the gel fraction of the pressure-sensitive adhesive layer described below can be easily adjusted to an appropriate range.
[0052] <Solvent> The pressure-sensitive adhesive composition of the present invention may contain a solvent. The solvent is not particularly limited, and examples thereof include aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as n-pentane, n-hexane, n-heptane, and n-octane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, cycloheptane, and cyclooctane; ethers such as diethyl ether, diisopropyl ether, 1,2-dimethoxyethane, dibutyl ether, tetrahydrofuran, dioxane, anisole, phenylethyl ether, and diphenyl ether; halogenated hydrocarbons such as chloroform, carbon tetrachloride, 1,2-dichloroethane, and chlorobenzene; esters such as ethyl acetate, propyl acetate, butyl acetate, and methyl propionate; ketones such as acetone, methyl ethyl ketone, diethyl ketone, methyl isobutyl ketone, and cyclohexanone; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; nitriles such as acetonitrile and benzonitrile; and sulfoxides such as dimethyl sulfoxide and sulfolane. The solvent may be used alone or in combination of two or more.
[0053] The content of the solvent is usually 0 to 90% by mass, and preferably 10 to 80% by mass, assuming that the entire pressure-sensitive adhesive composition of the present invention is 100% by mass.
[0054] <Other ingredients> The present composition may further contain other components in addition to the polymer (A) and the oligomer (B) as long as the effects of the present invention are not impaired. When other components are used in the present composition, the other components used in the present composition may each be one type or two or more types.
[0055] Other components include various additives such as tackifier resins, antistatic agents, silane coupling agents, antioxidants, UV absorbers, plasticizers, fine particles, and pigments. From the viewpoint of reducing the environmental impact, it is preferable to use raw materials derived from biomass. When the pressure-sensitive adhesive composition of the present invention contains other components other than the polymer (A), oligomer (B), crosslinking agent (C), and solvent, the other components may be contained in an amount of usually not more than 50 parts by mass, preferably not more than 40 parts by mass, and more preferably not more than 30 parts by mass, per 100 parts by mass of the polymer (A).
[0056] <Method of preparing the present composition> This composition can be obtained by mixing the above-mentioned components by a known method using a stirring device or the like. That is, the pressure-sensitive adhesive composition of the present invention can be obtained by mixing and stirring the components all at once or sequentially. There are no particular limitations on the stirring time, but it is sufficient to use a stirring time of about 10 to 120 minutes at room temperature from the viewpoints of workability and productivity.
[0057] <Adhesive layer> The pressure-sensitive adhesive layer is produced from the pressure-sensitive adhesive composition described above. For example, the pressure-sensitive adhesive layer can be obtained by promoting a crosslinking reaction in the pressure-sensitive adhesive composition, specifically by crosslinking the (meth)acrylic copolymer (A) with a crosslinking agent (C).
[0058] The conditions for forming the pressure-sensitive adhesive layer are, for example, as follows: The pressure-sensitive adhesive composition of the present invention is applied onto the release-treated surface of a substrate or a release-treated sheet (release sheet), and dried for usually 1 to 10 minutes, preferably 2 to 7 minutes, usually at 50 to 150°C, preferably 60 to 100°C, depending on the type of solvent, to remove the solvent and form a coating film. The thickness of the dried coating film is usually 5 to 125 μm, preferably 10 to 100 μm.
[0059] The pressure-sensitive adhesive layer is preferably formed under the following conditions: The pressure-sensitive adhesive composition of the present invention is applied onto the release-treated surface of a substrate or a release sheet, and a release sheet is attached onto the coating film formed under the above conditions. The composition is then cured for usually 3 days or more, preferably 7 to 10 days, under an environment of usually 5 to 60°C, preferably 15 to 40°C, and usually 5 to 70% RH, preferably 5 to 50% RH. When crosslinking is performed under the above curing conditions, a crosslinked body (network polymer) can be efficiently formed.
[0060] The pressure-sensitive adhesive composition can be applied by a known method, such as spin coating, knife coating, roll coating, bar coating, blade coating, die coating, or gravure coating, followed by coating and drying to a predetermined thickness.
[0061] The pressure-sensitive adhesive layer usually has a gel fraction of 50% by mass or more, preferably 60% by mass or more, and more preferably 70 to 99% by mass. If the gel fraction of the pressure-sensitive adhesive layer is within the above range, it is preferable in that excellent durability and appropriate cohesive force are obtained. It is also preferable in that the surface of the adherend is less likely to be contaminated.
[0062] From the viewpoint of reducing the environmental load, the pressure-sensitive adhesive layer preferably uses raw materials derived from biomass. The biomass degree of the pressure-sensitive adhesive layer is the weight ratio of the raw materials derived from biomass to the pressure-sensitive adhesive layer, and is calculated by the following formula. Biomass content [%] = (weight of biomass-derived raw materials / weight of adhesive layer) x 100 When the pressure-sensitive adhesive layer contains a biomass-derived raw material, the biomass degree may be any value, but is preferably high. The biomass degree of the pressure-sensitive adhesive layer is preferably 10% or more, more preferably 20% or more, and particularly preferably 30% or more.
[0063] <Surface protection film> The surface protective film of the present invention has a pressure-sensitive adhesive layer made from the pressure-sensitive adhesive composition of the present invention. The surface protection film of the present invention is less likely to cause zipping due to heat treatment, is less likely to contaminate the surface of the substrate, and has an excellent balance of heat resistance, holding power, etc., and can be suitably used in applications where these physical properties are required.
[0064] The surface protection film of the present invention has a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition for surface protection films. The surface protection film may further have a release sheet, and an example of the surface protection film includes a pressure-sensitive adhesive layer formed on one side of a substrate, and a release sheet attached to the other side of the pressure-sensitive adhesive layer not having the substrate.
[0065] As another example, a surface protection film may be obtained by providing a pressure-sensitive adhesive layer on both sides of a core layer, and then placing a substrate on one side of the pressure-sensitive adhesive layer and a release sheet on the other side of the pressure-sensitive adhesive layer. The substrate and core material are not particularly limited, and examples thereof include plastic, glass, woven fabric, nonwoven fabric, paper, etc. Examples of plastic include polycarbonate (PC), polymethyl methacrylate (PMMA), polyethylene terephthalate (PET), polypropylene (PP), acrylonitrile-butadiene-styrene copolymer (ABS), polyamide (nylon), etc.
[0066] In the surface protection film of the present invention, the difference between the contact angle after heat treatment and the initial contact angle in a water contact angle test described later is usually 12° or less, and preferably 10° or less. If the difference between the contact angle after heat treatment and the initial contact angle is within the above range, contamination of the adherend surface is unlikely to worsen even after, for example, a heat treatment step, which is preferable. The surface protection film of the present invention has a slippage of usually 1.5 mm or less, preferably 1.0 mm or less, in a holding power test described later. If the slippage is within the above range, problems such as lifting or peeling are unlikely to occur when the film is applied, which is preferable. The surface protection film having a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present invention exerts sufficient adhesive strength when applied, so that defects such as lifting and peeling are unlikely to occur, and when peeled off, the adherend is not contaminated and the surface protection film can be easily peeled off without zipping. The surface protection film of the present invention has a low-speed peel strength when applied at room temperature in a room temperature peel strength test described below, which is usually 0.75 N / 25 mm or less, preferably 0.05 to 0.75 N / 25 mm. The high-speed peel strength when applied at room temperature is usually 4.5 N / 25 mm or less, preferably 0.5 to 4.5 N / 25 mm. The difference between the high-speed peel strength and the low-speed peel strength at room temperature (high-speed peel strength - low-speed peel strength) is usually 4.45 N / 25 mm or less, preferably 4 N / 25 mm or less. The low-speed peel strength after heat treatment in a heat treatment peel strength test described below is usually 1.6 N / 25 mm or less, preferably 0.05 to 1.6 N / 25 mm. The high-speed peel strength after heat treatment is usually 8.5 N / 25 mm or less, preferably 0.5 to 8.5 N / 25 mm. The difference between the high-speed peel strength and the low-speed peel strength after heat treatment is usually 8.45 N / 25 mm or less, preferably 8 N / 25 mm or less.
[0067] The low-speed peel strength and the high-speed peel strength were measured according to the method described in the examples.
[0068] The uses of the surface protective film of the present invention are not particularly limited, but it can be suitably used as a surface protective film for protecting and shatterproofing plastics and glass, a protective film for optical members such as polarizing plates, and a protective film for electronic components and electronic devices such as electronic substrates. EXAMPLES
[0069] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0070] [Glass transition temperature (Tg)] The glass transition temperature (Tg) of the copolymer obtained in the following Production Examples was calculated by the following Fox's formula.
[0071] Fox formula: 1 / Tg=(W1 / Tg1)+(W2 / Tg2)+…+(Wm / Tgm) W1+W2+…+Wm=1 In the above formula, Tg is the glass transition temperature (unit: K) of the copolymer, Tg1, Tg2, ..., Tgm are the glass transition temperatures (unit: K) of homopolymers formed from each monomer, and W1, W2, ..., Wm are the mass fractions of the structural units derived from each monomer in the entire copolymer. The mass fractions of the structural units derived from each monomer can be determined by the ratio of each monomer to the total monomers used in the synthesis of the copolymer.
[0072] When calculating the Fox formula, the glass transition temperature (Tg) of the homopolymer formed from each monomer can be, for example, the value described in Polymer Handbook Fourth Edition (Wiley-Interscience 2003).
[0073] [Weight average molecular weight (Mw)] The weight average molecular weight (Mw) of each polymer was analyzed by gel permeation chromatography (GPC) and calculated in terms of polystyrene under the following conditions. Measuring device: HLC-8320GPC (Tosoh Corporation) GPC column configuration: The following five columns (all manufactured by Tosoh Corporation) (1) TSKgel HxL-H (guard column) (2) TSKgel G7000HxL (3) TSKgel GMHxL (4) TSKgel GMHxL (5) TSKgel G2500HxL ·Flow rate: 1.0mL / min Column temperature: 40℃ Sample concentration: 1.5% (w / v) (diluted with tetrahydrofuran) Mobile phase solvent: Tetrahydrofuran Standard polystyrene equivalent
[0074] [Synthesis Example 1] A reactor equipped with a stirrer, reflux condenser, thermometer, and nitrogen inlet tube was charged with 90 parts by mass of 2-ethylhexyl acrylate (2EHA), 6 parts by mass of methyl acrylate (MA), 4 parts by mass of acrylic acid (AA), and 100 parts by mass of ethyl acetate, and the temperature was raised to 70°C while introducing nitrogen gas. Next, 0.15 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) was added, and a polymerization reaction was carried out for 4 hours at 75 to 76°C under a nitrogen atmosphere to obtain a polymer (A-1) with a Tg of -62.6°C and Mw of 550,000.
[0075] [Synthesis Examples 2-13, 15-18] Polymers (A-2) to (A-13) and polymers (cA-1) to (cA-4) were obtained in the same manner as in Synthesis Example 1, except that the types and amounts of monomers used were changed as shown in Table 1. The Tg and Mw of the obtained polymers are also shown in Table 1.
[0076] [Synthesis Example 14] The types and amounts of monomers used were changed as shown in Table 1, and the amount of AIBN used was changed to 0.1 parts by mass. The procedure was the same as in Synthesis Example 1, except that a polymer (A-14) having a Tg of -60.1°C and an Mw of 1,000,000 was obtained.
[0077] [Synthesis Example 19] A reactor equipped with a stirrer, reflux condenser, thermometer, and nitrogen inlet tube was charged with 95 parts by mass of methyl methacrylate (MMA), 5 parts by mass of dimethylaminoethyl acrylate (DMAEA), and 100 parts by mass of toluene, and the temperature was raised to 90° C. while introducing nitrogen gas. Next, 3 parts by mass of AIBN was added dropwise over 2 hours, and then 1 part by mass of AIBN was added and reacted for 5 hours under reflux to obtain a polymer (B-1) with Tg 99.4° C. and Mw 5000.
[0078] [Synthesis Example 20] A reactor equipped with a stirrer, reflux condenser, thermometer, and nitrogen inlet tube was charged with 95 parts by mass of methyl methacrylate (MMA), 5 parts by mass of dimethylaminoethyl acrylate (DMAEA), and 100 parts by mass of toluene, and the temperature was raised to 90° C. while introducing nitrogen gas. Next, 1 part by mass of AIBN was added dropwise over 2 hours, and then 1 part by mass of AIBN was added and refluxed for 5 hours to obtain a polymer (B-2) with Tg 99.4° C. and Mw 20,000.
[0079] [Synthesis Example 21] A reactor equipped with a stirrer, reflux condenser, thermometer, and nitrogen inlet tube was charged with 95 parts by mass of methyl methacrylate (MMA), 5 parts by mass of dimethylaminoethyl acrylate (DMAEA), and 100 parts by mass of toluene, and the temperature was raised to 90° C. while introducing nitrogen gas. Next, 0.5 parts by mass of AIBN was added dropwise over 2 hours, and then 1 part by mass of AIBN was added and refluxed for 5 hours to obtain a polymer (B-3) with Tg 99.4° C. and Mw 70,000.
[0080] [Synthesis Examples 22-27] Polymers (B-4) to (B-7) and polymers (cB-1) to (cB-2) were obtained in the same manner as in Synthesis Example 20, except that the types and amounts of monomers used were changed as shown in Table 2. The Tg and Mw of the obtained polymers are also shown in Table 2.
[0081] [Table 1] 2EHA: 2-Ethylhexyl acrylate NOAA: Normal octyl acrylate (biomass content 70%) BA: normal butyl acrylate MA: Methyl acrylate MMA: Methyl methacrylate EMA: Ethyl methacrylate AA: Acrylic acid
[0082] [Table 2] DMAEA: Dimethylaminoethyl acrylate AM: Acrylamide ACMO: Acryloylmorpholine
[0083] [Example 1] [Preparation of Adhesive Composition] A pressure-sensitive adhesive composition was obtained by adding 4 parts by mass of the polymer (B-2) obtained in Synthesis Example 20 and 2.5 parts by mass of an epoxy-based crosslinking agent E-50C (manufactured by Soken Chemical & Engineering Co., Ltd.) to 100 parts by mass of the polymer (A-1) obtained in Synthesis Example 1. The parts added of each component indicate the solid content.
[0084] [Preparation of adhesive sheet] The degassed pressure-sensitive adhesive composition was applied onto a release-treated polyethylene terephthalate (PET) film using a doctor blade, and dried for 3 minutes at 80° C. to form a coating film with a dry thickness of 25 μm. A release-treated PET film was further attached to the side of the coating film opposite to the side to which the PET film was attached, and the coating film was left to stand for 7 days in a 23° C. / 50% RH environment to cure, thereby obtaining a pressure-sensitive adhesive sheet having a 25 μm-thick pressure-sensitive adhesive layer sandwiched between two PET films.
[0085] [Preparation of surface protection film] The obtained adhesive composition was applied onto a 38 μm-thick PET film substrate and dried at 80° C. for 3 minutes to form an adhesive layer with a dry thickness of 20 μm. Next, a release-treated PET film was attached onto the adhesive layer, and the adhesive layer was aged for 7 days in a 23° C. / 65% RH environment to obtain a surface protection film.
[0086] [Examples 2 to 26, Comparative Examples 1 to 8] Except for changing the blending compositions as shown in Tables 3 to 5, pressure-sensitive adhesive sheets and surface protection films were obtained in the same manner as in Example 1.
[0087] [Measurement of gel fraction] Approximately 0.1 g of the adhesive layer was collected from the prepared adhesive sheet and placed in a sample bottle, 30 mL of ethyl acetate was added, and the mixture was shaken for 4 hours. The contents of the sample bottle were then filtered through a 200-mesh stainless steel wire screen, and the residue on the screen was dried at 100°C for 2 hours to measure the dry weight. The gel fraction of the adhesive layer was calculated using the following formula. Gel fraction (%) = (dry weight / weight of adhesive layer) x 100
[0088] [Water contact angle] The obtained surface protection film was cut into a size of 50 mm x 50 mm to prepare two test pieces. The peel-treated PET film of one test piece was peeled off, and the exposed adhesive layer was attached to the surface of the PET film (Diafoil T680E100: manufactured by Mitsubishi Plastics) fixed to a support that was not easily adhesively treated, and pressed by rolling it back and forth three times with a 2 kg roller. After standing at 23 ° C for 20 minutes, the test piece was peeled off from the PET film, and ion-exchanged water filled in a syringe was dropped on the exposed PET film surface at a flow rate of 1 μL and a flow rate of 0.5 μL / s, and the contact angle of the PET film was measured at 23 ° C with a contact angle meter (manufactured by Dataphysics, OCA15EC) (initial contact angle).
[0089] The other test piece was peeled off from the release-treated PET film, and the exposed adhesive layer was attached to the surface of the PET film (Diafoil T680E100: manufactured by Mitsubishi Plastics) that was fixed to a support and was not treated for easy adhesion, and pressed with a 2 kg roller three times. After being left to stand at 23 ° C for 20 minutes, it was heat-treated at 105 ° C for 1 hour. After being left to stand for another hour at 23 ° C, the test piece was peeled off from the PET film, and ion-exchanged water filled in a syringe was dropped on the exposed PET film surface at a flow rate of 1 μL and a flow rate of 0.5 μL / s, and the contact angle of the PET film was measured with a contact angle meter at 23 ° C (contact angle after heat treatment). The higher the water contact angle, the more the PET film surface is contaminated with components derived from the adhesive layer. The water contact angle of the PET film before the surface protection film was attached was 69.5°.
[0090] [Holding force] In accordance with JIS Z 0237:2009, a surface protection film cut to a width of 20 mm was attached to a stainless steel plate so that an area of 20 mm x 20 mm was in contact with the plate, and the film was left for 1 hour under a load of 1 kg at a temperature of 80°C, after which the amount of displacement was observed. Note that "X minutes ↓" in the table indicates that the film fell after X minutes.
[0091] [Room temperature peel strength] The obtained surface protection film was cut to 25 mm x 150 mm, and the peel-treated PET film was peeled off from each piece, and the pieces were attached to a stainless steel plate. The pieces were left in a 23°C / 50% RH environment for 20 minutes. One end was then pulled in a 180° direction, and the force required for peeling was measured. Note that a tensile speed of 0.3 m / min was defined as low-speed peeling, and a tensile speed of 30 m / min was defined as high-speed peeling.
[0092] [Peeling strength after heat treatment] The obtained surface protection film was cut to 25 mm x 150 mm, and the peel-treated PET film was peeled off from each piece, and the pieces were attached to a stainless steel plate. The pieces were then left in an environment at 105°C for 1 hour, and then left to stand in an environment at 23°C for another 1 hour. One end was then pulled in a 180° direction, and the force required for peeling was measured. A tensile speed of 0.3 m / min was defined as low-speed peeling, and a tensile speed of 30 m / min was defined as high-speed peeling.
[0093] [Table 3]
[0094] [Table 4]
[0095] [Table 5]
[0096] The surface protection films of Examples 1 to 26 were less likely to contaminate the adherend surface and had excellent holding power. In addition, in peeling at room temperature and after heat treatment, the films showed appropriate peeling power in low-speed and high-speed peeling, and zipping was suppressed during high-speed peeling after heat treatment, and thus had an excellent balance of adhesive properties. On the other hand, in Comparative Example 1, which used polymer (cA-1) not containing monomer (a1), the high-speed peel force after heat treatment was excessively high and the holding force was insufficient, and the balance of adhesive properties as a surface protection film was insufficient. Comparative Example 2, which used the polymer (cA-2) not containing the monomer (a1), had an excessively high high-speed peel force after heat treatment. Comparative Example 3, which used the polymer (cA-3) containing 20 parts by mass or more of the monomer (a1), had an excessively high high-speed peel strength after heat treatment. In Comparative Example 4, which used a polymer (cA-4) having a Tg exceeding −25° C., the high-speed peel force after heat treatment was excessively high, and zipping occurred during high-speed peeling. Comparative Example 5, which did not contain oligomer (B), had excessively high peel strengths at low and high peel speeds both at room temperature and after heat treatment. In Comparative Example 6, which contains more than 40 parts by mass of oligomer (B) per 100 parts by mass of polymer (A), zipping occurred during high-speed peeling at room temperature and after heat treatment. In addition, since the difference between the contact angle after heat treatment and the initial contact angle in the water contact angle test was large, contamination of the adherend surface was likely to worsen after the heat treatment process. Comparative Example 7, which used oligomer (cB-1) not containing monomer (b1), had an excessively high high-speed peel force after heat treatment, and also had a large difference between the contact angle after heat treatment and the initial contact angle in the water contact angle test. In Comparative Example 8, which used an oligomer (cB-2) with a Tg of -25°C or less, the peel strengths in the low-speed peel and high-speed peel were excessively high both at room temperature and after heat treatment.
Claims
1. a (meth)acrylic polymer (A) which is a copolymer of a monomer mixture (a) containing 5% by mass or more and less than 20% by mass of an alkyl (meth)acrylate having an ester side chain with 1 to 3 carbon atoms, and which has a glass transition temperature (Tg) of -70°C or more and -25°C or less; A copolymer of a monomer mixture (b) containing a nitrogen atom-containing monomer, and a (meth)acrylic oligomer (B) having a glass transition temperature (Tg) of more than -25°C and not more than 200°C. Including, A pressure-sensitive adhesive composition for protecting a surface, comprising the (meth)acrylic oligomer (B) in an amount of more than 0 part by mass and not more than 40 parts by mass per 100 parts by mass of the (meth)acrylic polymer (A).
2. The monomer mixture (a) further comprises An alkyl (meth)acrylate having an ester side chain with 6 to 22 carbon atoms is contained in an amount of 50% by mass or more and less than 94% by mass, Carboxy group-containing monomer in the range of more than 1% by mass and not more than 10% by mass 2. The pressure-sensitive adhesive composition for protecting a surface according to claim 1, wherein the monomer mixture (a) is 100% by mass as a whole.
3. 2. The pressure-sensitive adhesive composition for protecting a surface according to claim 1, wherein the monomer mixture (b) contains the nitrogen atom-containing monomer in an amount of more than 0 mass% and not more than 10 mass% (wherein the entire monomer mixture (b) is taken as 100 mass%).
4. A pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition for protecting a surface according to claim 1 , which has a biomass ratio of 10% or more.
5. A surface protection film having a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition for surface protection according to claim 1.
6. The surface protection film according to claim 5, which has a displacement of 1.5 mm or less after 1 hour of a holding strength test in accordance with JIS Z 0237:2009, with an application area of 20 mm x 20 mm, a test temperature of 80°C, and a load of 1 kg.
Citation Information
Patent Citations
Adhesive composition
JP1998310754A
Re-peelable adhesive tape
JP2000328016A